A new conceptualization of investor sophistication and its impact on herding and overconfidence bias - Ashutosh Yadav; Deepshikha Yadav; Ishan Kashyap Hazarika (Investment Management & Financial Innovations, 2022)
Despite the success of behavioral finance, the question of whether behavioral biases persist in the face of expertise is an oft-expressed concern. It becomes pertinent to explore if investor sophistication is associated with behavioral biases, as traders gain sophistication with experience and knowledge. The current study explores this relationship by proposing a new conceptualization of investors’ sophistication via the processes of learning and competition. The study empirically explores if herding and overconfidence biases are related to learning and competition, and thus, with investors’ sophistication via these aspects. Using data from equity investors from India (n = 257), the study employs ANOVA and multiple regression analysis through indicator function to form dummy variables for different categories. The results of the study conclude that diversification is significantly related to both the biases using ANOVA (F(3,253) = 3.081; p < 0.05) as well as multiple regression (p < 0.05). The other variables considered are found to be non-significant (p > 0.05) for both the biases. The study controls for all the other observed variables of the conceptual model to find out the effect of the change in the observed variables on the level of investor sophistication, making this study a novel and a distinct attempt.